2017
DOI: 10.1016/j.tins.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Membrane-Initiated Signaling in the Brain Mediates Reproduction

Abstract: Over the past few years, our understanding of estrogen signaling in the brain has expanded rapidly. Estrogens are synthesized in the periphery and in the brain, acting on multiple receptors to regulate gene transcription, neural function, and behavior. Various estrogen-sensitive signaling pathways often work in concert within the same cell, increasing the complexity of the system. In females, estrogen concentrations fluctuate over the estrous/menstrual cycle, dynamically modulating estrogen receptor expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 119 publications
1
35
0
Order By: Relevance
“…These findings suggest there may be dimorphisms in ER␣ trafficking. Male/female differences in the expression of proteins that enable ER␣ membrane delivery and signaling have been reported (Meitzen et al, 2017), but the levels of these proteins near the synapse are not known. Related to compartmentalization, it should be noted that the FDT technique used here allows for measures of ER␣ colocalized with PSD-95, and thus positioned near the synapse in the postsynaptic compartment, but does not describe ER␣ levels deeper within the spine or in membrane-bound versus cytosolic pools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest there may be dimorphisms in ER␣ trafficking. Male/female differences in the expression of proteins that enable ER␣ membrane delivery and signaling have been reported (Meitzen et al, 2017), but the levels of these proteins near the synapse are not known. Related to compartmentalization, it should be noted that the FDT technique used here allows for measures of ER␣ colocalized with PSD-95, and thus positioned near the synapse in the postsynaptic compartment, but does not describe ER␣ levels deeper within the spine or in membrane-bound versus cytosolic pools.…”
Section: Discussionmentioning
confidence: 99%
“…Estrous staging of female rats and mice. For all females used, estrous cycle state was evaluated using vaginal smears collected by lavage and Nissl staining (McLean et al, 2012). For electrophysiological studies, the estrous cycle state was determined from samples collected at the time of killing and was evaluated after the analysis of electrophysiological recordings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HT POMC neurons have bidirectional connections with the HT KISS1 neurons driving acute sex hormone release [Backholer et al, 2010]. Estrogen yields BEND release from ARC to MPOA to promote lordosis, the innate female body posture for receptive copulation exhibited by most mammals [Micevych et al, 2017]. Sex-related consume innates are promoted by another endorphin opioid, endomorphin, which strongly activates MORs [Paredes, 2014].…”
Section: Consume: Beta-endorphin (Bend)mentioning
confidence: 99%
“…Copulation is a naturally occurring motivated behavior reliant on gonadal hormones. Earlier research has shown that structural neuronal plasticity could be at the basis of hormonal effects on sexual behavior (Micevych et al, 2017). For example, within the hypothalamus, estradiol appears to enhance neuronal connectivity, essential for lordosis (Meisel and Luttrell, 1990;Dewing et al, 2007;Christensen et al, 2011;Inoue et al, 2019).…”
Section: Introductionmentioning
confidence: 99%